Determinants of Shareholder Value in China's Banking Sector - LI, Zhuoyang (2016)
The aim of this study is to examine the effect of various determinants that may affect shareholder value in the Chinses banking sector. The determinants are classified by bank-specific factors, industry specific factors and macro-economic factors. A panel data set has been used for Chinese banks over the time period between 2004-2015. To account for heterogeneity and endogenous problems, OLS, FEM, REM and GMM are conducted one by one. In addition, another robust test applying different dependent variable and more explanatory variables is conducted. The estimation results show that bank size and inflation rate have a positive and significant impact on residual income, credit risk, leverage level and cost inefficiency affect residual income significantly in the anticipated way. Results from the GMM estimator show that the residual income in last time period has positive and significant impact on that in current time period. In addition, a positive and significant relationship between GDP growth rate and residual income has been founded. Evidence from the second robust test shows the same significant level for the explanatory variables applied previously on banks’ stock price, but the book value per share and earning per share do not seem explain the stock price well. There is no evidence that finds that the liquidity risk, income diversification and bank size dummy significantly affect residual income. This study sheds some lights on bank management, investment decisions and standard setting to some extent.